O método de tradução de João Ferreira de Almeida: O caso do Evangelho de Mateus - Cavalcante Filho, Jairo Paes (2013)
The classic Bible version by João Ferreira de Almeida is the most popular translation in the lusophone countries, even when the dynamic equivalence concept is the main driver in the production of new Bible translations. The original text, as produced by Almeida, never has been published, and so far no portion of his presumed manuscript version has been located. All of the first editions of Almeida s New Testament have been printed after a reviewing and approval by the Dutch Reformed Church authorities. This research develops a method to build a critical edition of the work of João Ferreira de Almeida, starting from what is known concerning Almeida s life and Bible translation history, his six first printed New Testaments and his Old Testament editions (XVIII century). Afterwards, the method is tested, producing a critical version of Matthew Gospel.